Job Crafting, a brain drain antidote in Public Universities in Nigeria - Ebuka, Arachie Augustine; Ngozi, Nzewi Hope; Obianuju, Chiekezie; Peace, Nwakoby Nkiru (Annals of Human Resource Management Research, 2022)
Purpose: This study examined job crafting (JC) and the role it could play in reducing brain drain in universities in Nigeria. Research Methodology: -it adopted a survey research design, with its population consisting of 8051 academic staff of six selected universities in the Southeast. A sample size of 367 was determined using Krejcie and Morgan’s (1970) formula. The source of data collection was a structured questionnaire. A combination of descriptive and inferential statistics was used for data analysis. Results–among others, the result revealed that there are ways academics can craft their jobs in universities in Nigeria and that there is a significant mean difference among the various dimensions of job crafting activities carried out by academics. Limitations: The study looked at a particular section of Nigeria, thereby, limiting the inference power of the findings. Contributions: None of the previous studies seem to have focused solely on how job crafting is done and which one is more prominent among lecturers in Nigeria. Similarly, none also appear to have looked at job crafting and how it can be used to reduce brain drain in Nigerian Universities.